A Study on Public-Private Partnerships with reference to Municipality of Korca, Albania - Dhimitri, Eva (European Journal of Multidisciplinary Studies, 2018)
Public private partnership is in central of good governance with emphasis on efficiency, inclusion and partnership. The main point is that the partnership does not mean competition, but cooperation between different organizations. It means a formal link between public and private sectors and involves cooperation in planning, financing and implementation of joint projects to achieve common goals. The state assists in its mission from many actors, and above all from the private sector. This article aims to explore the concept of Public Private Partnership as an approach that provides mutual benefits to both public and private sectors. Albania has great potential to develop successful forms of Public Private Partnerships and the public interest is quite high, however, it is important to learn from own successful and not successful experiences of the past, as well as from the experience of the others. This study focused in experience of Municipality of Korca, main region in southeast of Albania.